Investigating Diagnostic and Treatment Barriers in Cancer Care: A Rural Perspective from Western Maharashtra, India - Nagar, Akash; Vishwakarma, Kavita; Nair, Gayatri R.; R., Akhil; Madamanchi, Divya (Indian Journal of Medical and Paediatric Oncology, 2025)
Introduction Noncommunicable diseases, particularly cancer, are increasingly burdening India's health care system. Despite the implementation of various national cancer control programs, notable barriers to timely diagnosis and treatment persist, especially in rural regions.Objectives This study aims to identify these barriers and assess diagnostic and treatment intervals among cancer patients in rural Western Maharashtra.Materials and Methods A cross-sectional study was conducted at a tertiary cancer hospital from January to March 2024. Histopathologically confirmed patients with cancer (aged ≥ 18 years) who attended the radiotherapy and chemotherapy outpatient departments for treatment were included. Data was collected using structured interviews, focusing on sociodemographic factors, diagnostic intervals (from first symptom to final diagnosis), and treatment intervals (from final diagnosis to treatment initiation). Statistical analyses were performed using MedCalc software.Results Out of 127 patients analyzed, the mean age was 53.4 years, with 68.5% being female. The majority resided in rural areas (52.0%). Breast cancer (26.8%), lip and oral cavity cancer (15.0%), and cervical cancer (10.2%) were the most prevalent among patients. The median total interval in diagnosis was 86 days, with a median diagnostic interval of 61 days and a median treatment interval of 8 days. Substantial barriers to timely diagnosis included misconceptions about symptom severity, neglect, and lack of knowledge about where to seek care. Rural residency and diagnosis of the first doctor consulted were significantly associated with longer diagnostic intervals.Conclusion The study identified critical barriers to timely cancer diagnosis and treatment in rural Western Maharashtra, highlighting the need for increased awareness, better access to health care, and streamlined diagnostic processes. Addressing these challenges through targeted strategies can potentially reduce delays and improve cancer care outcomes, enhancing survival rates and quality of life for patients in this region. This study highlights the urgency for health care policymakers to prioritize and address these barriers to improve cancer care in rural India.
Keywords: barriers; cancer; diagnostic interval; noncommunicable diseases; treatment interval